On the Handing over of the Exhibits of the 1900 Paris Exposition. Correspondence among the Lithuanian Alliance of America, Morta Zauniūtė, and Jonas Basanavičius (1905–1909) - Vaicekauskas, Mikas (Literatūra, 2024)
Rallied by national revival, Lithuanians also presented their display at the 1900 Paris Exposition. The Lithuanian section of the Paris Exposition was opened on 14 May. Since it was impossible to have a separate pavilion for political reasons, it was shown in the ethnographic part of the exposition at the Trocadéro Museum of Ethnography, that is, at the Trocadéro Palace. It had been agreed that the exposition would be ethnographic in nature. However, taking the key interests of the participation in the exhibition into account, the organisers made effort to organise a section on the Lithuanian press, which attracted the attention of the international community to the ban on the Lithuanian press. The Lithuanian exhibition was a success and was covered by the foreign press; it closed on 12 November. In addition to the extremely complex matters of its organisation, the issues of its liquidation – meeting the obligations of the exhibition, preparation of reports, using the surplus funds, gifting the exhibits, returning the borrowed exhibits, handling the remaining exhibits, etc. – arose after it. When eventually a decision was made to hand the remaining exhibits over to the Lithuanian Alliance of America and later to the Lithuanian Science Society, this was not carried out smoothly and without delay. After lengthy journeys around the world and in Europe, these remaining exhibits reached Vilnius and were integrated in memory institutions; they became accessible to the general public, and have remained such up until now. The sources available – the correspondence between the organisations and individuals involved in this matter and publications in the press, which are currently stored at Vilnius University Library and at the Institute of Lithuanian Literature and Folklore – make it possible to introduce the history of the transfer of the exhibits consistently, while also covering some individual and psychological nuances.
Keywords: 1900 Paris Exposition; Lithuanian Alliance of America; Lithuanian Science Society; Jonas Basanavičius; Morta Zauniūtė; exhibits; books